Accurate 5 Accounting Application Training for Students of SMA Negeri 2 Lembang, West Bandung Regency - Hasanah Tisna Amijaya; Ganjar Nurul Fajar; Rinawati Rinawati (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2024)
The Head of the Study Program, lecturers, and the Accounting Computerization Student Association of STMIK Mardira Indonesia's Class of 2020 and 2021 have formed a community service team to tackle the problem of SMAN 2 Lembang students' need for comprehension when it comes to using applications The team's primary focus in this project was creating and instructing accounting students on how to utilize the Accurate 5 Accounting Application. This project's primary goal is to increase students' comprehension of and proficiency with accounting software, which is crucial for equipping them with obstacles in the workplace. Practice-based learning and practical training are the approaches employed. The project has led to a notable improvement in the student's comprehension and proficiency with the Accurate 5 Application. In conclusion, SMAN 2 Lembang students' technical abilities have improved significantly due to this community service project, particularly in the area of digital accounting, and it is anticipated that these gains will last for a long time.